Pengaruh Sistem dan Harga Terhadap Kinerja Penerapan E-Ticketing di Pelabuhan Roro Bengkalis - S, Suharyono (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
The purpose of our research is to study the application of the Roro e-ticket information system from the aspect of user needs. In determining the variables of the e-ticket information system, quantitative methods will be carried out on aspects of customer needs, technical aspects using descriptive methods. The time of the research was carried out in 2022 for 4 months. Located in Roro Harbor, Bengkalis Regency. The number of samples in this study were 100 respondents who used roro in Bengkalis Regency. The research variables, namely: system (X1), price (X2), and performance (Y). The results of this study have proven that partially or simultaneously the variables X1 (system) and X2 (price) affect the Y variable (performance). The community of roro users in Bengkalis Regency hopes that the plan for implementing e-tickets in roro is no longer just a discourse but has yet to be realized. This is in accordance with the results of a survey that has been conducted. With the application of e-tickets, the roro crossing service in Bengkalis is increasingly optimal. However, the public hopes that the application of e-tickets will not affect the increase in ticket prices. Do not let the e-ticket, users are even burdened with additional costs..